Adapting to disruption of research during the COVID-19 pandemic while testing nonpharmacological approaches to pain management. Issue 4 (4th September 2020) - Coleman, Brian C; Kean, Jacob; Brandt, Cynthia A; Peduzzi, Peter; Kerns, Robert D
Abstract: The COVID-19 pandemic has slowed research progress, with particularly disruptive effects on investigations of addressing urgent public health challenges, such as chronic pain. The National Institutes of Health (NIH) Department of Defense (DoD) Department of Veterans Affairs (VA) Pain Management Collaboratory (PMC) supports 11 large-scale, multisite, embedded pragmatic clinical trials (PCTs) in military and veteran health systems. The PMC rapidly developed and enacted a plan to address key issues in response to the COVID-19 pandemic. The PMC tracked and collaborated in developing plans for addressing COVID-19 impacts across multiple domains and characterized the impact of COVID-19 on PCT operations, including delays in recruitment and revisions of study protocols. A harmonized participant questionnaire will facilitate later meta-analyses and cross-study comparisons of the impact of COVID-19 across all 11 PCTs. The pandemic has affected intervention delivery, outcomes, regulatory and ethics issues, participant recruitment, and study design. The PMC took concrete steps to ensure scientific rigor while encouraging flexibility in the PCTs, while paying close attention to minimizing the burden on research participants, investigators, and clinical care teams. Sudden changes in the delivery of pain management interventions will probably alter treatment effects measured via PMC PCTs. Through the use of harmonized instruments and surveys, we are capturing these changes and plan to monitor the impact on research practices, as well as on health outcomes. Analyses of patient-reported measures over time will inform potential relationships between chronic pain, mental health, and various socioeconomic stressors common among Americans during the COVID-19 pandemic.